Comparação de três técnicas de Recovery sobre a percepção da dor e esforço e na performance em praticantes de crossfit® após um treino: um ensaio controlado aleatorizado - Sampaio, Tailândia Viana (2022)
Post-exercise recovery is understood as the process of restoration of body systems to its basal condition providing balance and preventing the installation of injuries. Recovery is considered a multifactorial restoration process and is a comprehensive term that includes different recovery modalities, which are divided between active, passive, and proactive recovery methods. The assertive choice of recovery techniques is extremely important to allow the athlete to act during the next training session rested, healthy and injury-free. The mechanisms involving the effects of recovery are dependent on the technique used. However, most of them act on muscle damage and inflammation induced by exercise. The literature already shows us that there are positive effects in the use of techniques such as active recovery, massage, compression boot, immersion, contrast bath and cryotherapy in reducing Delayed Onset Muscle Soreness (DOMS) and only techniques such as massage and compression boot in recovery as fatigue. What is still little addressed in the literature is the comparison of the efficacy of these techniques among themselves, because this information could facilitate the choice of the best procedures by professionals for adequate recovery. Therefore, the aim of this study is to compare the effectiveness of manual massage, percussion gun and pneumatic compression boot on pain, subjective perception of effort and performance in simple horizontal jump in CrossFit® practitioners after a workout.